To Initiate or to Terminate: Effects of Endurance Status and Hydraulic Factors on Fish Upstream Attempt Behavior Under High-Flow Conditions - Kaixiao Chen; Xiaogang Wang; Yun Li; Jingjuan Li; Lijian Wu; Jianzhang Lv; Yongzeng Huang; Biao Wang; Guoxiu Shang (Fishes, 2026)
Understanding the upstream-attempt behavior of fish in high-flow environments is important for refining behavioral simulations, optimizing fish-passage design, and protecting aquatic ecosystems. This study investigates Schizothorax oconnori, an endemic fish in the Yarlung Tsangpo River on the Qinghai–Tibet Plateau, using a multi-model analytical framework integrating a generalized linear mixed-effects model, Random Forest, SHapley Additive exPlanations, and GeoDetector. Results showed that remaining endurance and nominal flow velocity were positively associated with fish upstream-attempt initiation. Attempt termination reflected endurance depletion, initial endurance, and hydraulic variability. Model-predicted termination probability increased markedly when (i) cumulative endurance consumption during the current attempt exceeded ~11% or (ii) fish began an attempt with an initial endurance status below ~95%. These model-derived change points represent within-attempt endurance depletion and reduced endurance available at attempt initiation, respectively. Across attempt sequences, the dominant explanatory factors showed an apparent shift from physiological condition during the first attempt to hydraulic variability during subsequent attempts. This sequence-related pattern is consistent with behavioral adjustment based on repeated experience in the flow environment, although cumulative fatigue, stress, individual differences, and experimental procedures may also contribute. Hydraulic-variability metrics along the trajectory showed greater explanatory importance than several instantaneous hydraulic variables, and physiological condition and hydraulic variability together enhanced explanatory power. This study provides a quantitative multi-model framework for analyzing upstream-attempt behavior and offers a scientific basis for refining behavioral simulations and optimizing fish-passage facilities.